Flexural Characteristics of Hollow One Way-Ferrocement Slabs - Ismael, Bashar H.; Ali, Ziadoon Mohsin; Hama, Sheelan Mahmoud; Aljumaily, Mustafa Mohammed; Alshami, Abeer W.; Mohammed, Shahad Shaker (Engineering, Technology & Applied Science Research, 2025)
In this study, five hollow one-way Ferrocement slabs were fabricated, cast, and tested under a four-point loading system. The ferrocement slabs were voided by waste plastic bottles. The main employed parameters were the void presence, void ratio for the waste plastic bottles, and fiber percentage. The waste plastic bottle void method relied on a hollow tube of steel wire mesh that was then filled with waste plastic bottles and installed at the mid-height of slab thickness aiming for the low stress position within slab depth. The ultimate load capacity, flexural stiffness and ductility, crack width, and profile deflection were measured and analyzed. The study demonstrated that the ferrocement voided slab load capacity was affected by the voids compared to the reference specimen, namely the ferrocement solid slab. However, the voided slabs using 1% Polypropylene (PP) Fibers demonstrated a good performance, which was approximately identical to that of the solid slab. From the results, it can be concluded that the addition of PP fibers to empty plastic bottle hollow slabs is an excellent method to increase the latter's total flexural stiffness. Compared to the solid slab, the voids in the slabs not only decreased the dead load, but also ductility and stiffness. Moreover, adding fibers improved these qualities making them similar to those of the original slab. Furthermore, it was observed that when using two lines of hollow plastic tube, the ultimate load capacity dropped by approximately 18.5% compared to that of the solid slab.